2021
DOI: 10.1002/ejp.1787
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between oral paracetamol and nefopam in a murine model of postoperative pain

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…A single dose of nefopam might be insufficient to control moderate pain in an ACDF or lumbosacral spine operation. In a previous study, [ 22 ] an animal model showed a synergistic antinociceptive interaction between low doses of nefopam and paracetamol to treatment of postoperative hypersensitivity to peripheral stimuli. In both groups, all patients received oral paracetamol which may cover mild to moderate postoperative pain after anterior cervical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A single dose of nefopam might be insufficient to control moderate pain in an ACDF or lumbosacral spine operation. In a previous study, [ 22 ] an animal model showed a synergistic antinociceptive interaction between low doses of nefopam and paracetamol to treatment of postoperative hypersensitivity to peripheral stimuli. In both groups, all patients received oral paracetamol which may cover mild to moderate postoperative pain after anterior cervical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies evaluating the efficacy of multimodal analgesia on PPP, however an example of its effectiveness can be seen in a breast cancer surgery trial, whereby pain and analgesic consumption was significantly reduced at 3 months in patients that received gabapentin, a mixture of local anesthetic cream, and ropivacaine wound infiltration ( 215 ). Pre-clinical models demonstrate analgesic synergy between clinically approved analgesics, as well as novel pharmacotherapies including a combination of selective Na v 1.7 inhibitors, with baclofen or opioids ( 124 , 216 ). A detailed summary of randomized controlled trials using pharmacological interventions to prevent the development of PPP can be found in the following review ( 202 ).…”
Section: Prevention and Treatment Of Pppmentioning
confidence: 99%